ASSESSING FISCAL EFFICIENCY IN INDONESIAN REGIONAL GOVERNMENT FINANCIAL MANAGEMENT: A SLACK-BASED MEASURE AND MALMQUIST INDEX APPROACH - Hans Victor Sitepu; Israfil Munawarah; Natanael Waraney Gerald Massie (Faculty of Economics and Business University of Mataram, 2026)
This study evaluates the fiscal efficiency of regional financial management in Indonesia during 2013–2023 and provides evidence to inform policy reform. Using panel data from 133 regencies/ municipalities in four populous provinces, this study applies output-oriented Data Envelopment Analysis (DEA) with Slack-Based Measure (SBM) and Malmquist Index models to measure static and dynamic fiscal efficiency. The findings show North Sumatra as the highest fiscal efficiency despite having the smallest average budgets, while West Java leads the fiscal performance frontier. The study calls for stronger central and provincial regulatory frameworks to improve spending allocation, absorption, and overall regional fiscal efficiency. It also contributes to the decentralization literature by offering evidence-based insights for adaptive and sustainable regional governance.